2016
DOI: 10.1111/jfs.12269
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Survival of Lactobacillus Acidophilus and Bifidobacterium Bifidum in Probiotic Yogurts Enriched by Barberry Extract

Abstract: This study investigated the effect of functional properties of barberry aqueous extract in different concentration of 4 and 5% (w/w) on the growth and survival of probiotic cultures (L. acidophilus, B. bifidum and an equal mixture of the two strains) in the set and stirred yogurt samples. The viable counts of L. acidophilus and B. bifidum in the set and stirred probiotic yogurts containing barberry extract were significantly higher than the control yogurt sample during the storage period. In a single strain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…L. acidophilus and B. bifidum probiotic bacteria were selected in this study as they are the most common probiotics reported to have beneficial health effects. Additionally, they have been used safely in several food products 48 . In accordance with Shanmugam et al 20 , upon the treatment with indomethacin, the body weight gain (see Supplementary Table S3 online) of the INDO group (34.67 g) significantly was less than the NC group (40.50 g).…”
Section: Resultsmentioning
confidence: 99%
“…L. acidophilus and B. bifidum probiotic bacteria were selected in this study as they are the most common probiotics reported to have beneficial health effects. Additionally, they have been used safely in several food products 48 . In accordance with Shanmugam et al 20 , upon the treatment with indomethacin, the body weight gain (see Supplementary Table S3 online) of the INDO group (34.67 g) significantly was less than the NC group (40.50 g).…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays consumers believe that foods can significantly contribute to their health and wellness (Mollet and Rowland, 2005; Hassani et al, 2016) and functional products meet this increasing demand of healthy diet, as they satisfy hunger and provide essential nutrients, but they can also prevent diseases and promote physical and mental wellness (Menrad, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, investigations on Lactobacillus plantarum have succeeded in attracting the interest of scientists owing to its beneficial effects on the host (Jones et al, ; Schwarzer et al, ) and high commercial value for dairy producers (Ciocia, McSweeney, Piraino, & Parente, ; Li et al, ). Some investigations have shown that TCM extracts can achieve a beneficial effect by promoting the growth of probiotics (El‐Sayed, Abdel‐Salam, Badran, & Ibrahim, ; Hassani, Sharifi, Mohammadi, & Hassani, ). For example, the generation time of L. plantarum , Lactobacillus casei and Lactobacillus rhamnosuss can be decreased in the presence of chicory extract (El‐Sayed et al, ).…”
Section: Introductionmentioning
confidence: 99%